FEATURES OF THE SENSE OF JUSTICE IN THE YOUTH OF DAGESTAN - N. A. Asvarov (Вестник Кемеровского государственного университета, 2015)
Article retractedThe paper presents the features of formation of the sense of justice and legal culture in Dagestan youth. On the basis of sociological poll the author identified the role of the regional factors that have positive influence on the process of formation of legal culture of the Dagestan youth; the author considers the formation of the sense of justice by means of organized legal education in educational institutions.